KARAKTERISTIK FLUKS MEMBRAN DALAM PROSES FILTRASI LIMBAH CAIR INDUSTRI PELAPISAN LOGAM - Fifia Zulfi (Jurnal Biofisika, 2014)
Environmental pollution that caused by electroplating wastewater can be solved by membrane technology. Chitosan and silica have been used widely in the wastewater treatment process and also easily formed into membranes. The purpose of this study is to analyze characteristics of membrane flux , which is one indicator of the quality of the performance of the membrane. The membranes used in the filtration process is made of chitosan and silica rice husk ( biosilika ) with inverse phase technique. Variations in the mass ratio of chitosan and biosilika are 1, 1.5, 2, and 3 for membrane A, B, C, and D respectively. The results of flux showed that the membrane flux decreased exponentially with increasing time. Flux caharcteristics of membrane B is better than others because the average flux and porosity in the electroplating wastewater filtration is higher than the others, namely 19115.62 L/m2hours and 87.79 % respectively. The mechanism of membrane fouling on chitosan - biosilika has caused by blocking of a number of membrane pores is described by curves fitting of flux decline to the experimental data.